Optimal timing and treatment strategy for pancreatic cancer. Issue 3 (29th May 2020) - Gamboa, Adriana C.; Rupji, Manali; Switchenko, Jeffrey M.; Lee, Rachel M.; Turgeon, Michael K.; Meyer, Benjamin I.; Russell, Maria C.; Cardona, Kenneth; Kooby, David A.; Maithel, Shishir K.; Shah, Mihir M.
Abstract: Background: For pancreatic adenocarcinoma (PDAC), no studies have established any association between earlier treatment initiation and long‐term outcomes. In addition, an optimal type of initial treatment for the localized disease remains ill‐defined. Methods: Patients in the National Cancer Database (2004‐2015) with clinical stage I (CS‐I) and II (CS‐II) PDAC who underwent curative‐intent resection were included. Optimal time from diagnosis‐to‐treatment including neoadjuvant chemotherapy, neoadjuvant chemoradiation, or upfront surgery was assessed. An optimal type of treatment was evaluated. The primary outcome was overall survival (OS). Results: Among 29 167 patients, starting any treatment within 0 to 6 weeks was associated with improved median OS compared with 7 to 12 weeks (21.0 vs 20.1 months; P = .004). This persisted when accounting for sex, race, and Charlson‐Deyo score (hazard ratio [HR], 0.94; P = 0.02) and on subset analysis for CS‐I (23.5 vs 21.8 months; P = .04) and CS‐II (19.4 vs 18.3 months; P = .03). Neoadjuvant chemotherapy was associated with improved OS compared with neoadjuvant chemoradiation (25.6 vs 22.7 months; P < .0001) or US (25.6 vs 20.1 months; P < .0001) even when accounting for sex, race, and Charlson‐Deyo score (neoadjuvant chemoradiation: HR, 0.86; P < .001; US: HR, 0.79; P < .001). This improvement persisted in subset analysis with NC compared with neoadjuvant chemoradiation (CS‐I: 28.6 vs 25.0 months; CS‐II: 25.0 vs 22.9 months; both P < .0001) and to US (CS‐I: 28.6 vs 22.9 months; CS‐II: 24.7 vs 18.4 months; both P < .0001). On multivariable analysis for each CS‐I/CS‐II, NC remained associated with 20% improved survival compared with neoadjuvant chemoradiation or upfront surgery. Conclusions: For PDAC, initiation of therapy within 6 weeks from diagnosis is associated with improved survival, with neoadjuvant chemotherapy associated with the best survival compared with neoadjuvant chemoradiation or upfront surgery.